PERAN KEGIGIHAN DALAM HUBUNGAN GROWTH MINDSET DAN SCHOOL WELL-BEING SISWA SEKOLAH MENENGAH - Fatin Rohmah Wahidah; Lucia R M Royanto (Jurnal Psikologi TALENTA, 2019)
This study investigates the relationship between school well-being, growth mindset, and grit. The subjects involved in this study are students from grade 12 in high public and private schools in Purbalingga, Central Java (n=418). The research method used is quantitative method with data collection through three questionnaires, i.e., School Well-Being Scale (32 items, α=0.853); Mindset Scale (20 items, α=0.804); and Grit Scale for Children and Adult (12 items, α=0.774). Results indicated a positive affact growth mindset on school well-being, a positive affact growth mindset on grit, and confirmed the mediating role of grit. It was concluded that the effect of growth mindset on school well-being of senior high school students in Purbalingga was mediated by grit. Growth mindset in students predicts higher school well-being through the enhancement of grit. Thus, giving intervention of growth mindset and grit can be carried out by school to improve students’s school well-being.Keywords: grit, growth mindset, high schools, school well-being Tujuan dari penelitian ini adalah untuk mengetahui hubungan school well-being, growth mindset, dan kegigihan. Partisipan yang terlibat adalah siswa kelas 12 sekolah menangah atas dari sekolah negeri dan sekolah swasta di daerah Purbalingga, Jawa Tengah (n=418). Metode penelitian yang digunakan adalah metode kuantitatif dengan pengumpulan data melalui tiga kuesioner, yaitu skala School Well-Being (32 aitem, α=0.853); skala Mindset (20 aitem, α=0.804); and Grit Scale for Children and Adult (12 aitem, α=0.774). Hasil penelitian menunjukkan adanya pengaruh positif growth mindset terhadap school well-being, pengaruh positif growth mindset terhadap kegigihan, dan kegigihan terkonfirmasi sebagai mediator. Dapat disimpulkan, pengaruh growth mindset terhadap school well-being pada siswa sekolah menengah di Purbalingga dimediasi oleh kegigihan. Growth mindset pada siswa memprediksi school well-being, melalui pengembangan kegigihan. Oleh karena itu, pemberian intervensi dengan menyasar growth mindset dan kegigihan disarankan dapat dilakukan sekolah untuk meningkatkan school well-being siswa.Kata kunci: growth mindset, kegigihan, school well-being, sekolah menengah atas